2020
DOI: 10.3390/nu12041059
|View full text |Cite
|
Sign up to set email alerts
|

Urtica dioica Whole Vegetable as a Functional Food Targeting Fat Accumulation and Insulin Resistance-a Preliminary Study in a Mouse Pre-Diabetic Model

Abstract: The shoot of Urtica dioica is used in several cultures as a vegetable or herb. However, not much has been studied about the potential of this plant when consumed as a whole food/vegetable rather than an extract for dietary supplements. In a 12-week dietary intervention study, we tested the effect of U. dioica vegetable on high fat diet induced obesity and insulin resistance in C57BL/6J mice. Mice were fed ad libitum with isocaloric diets containing 10% fat or 45% fat with or without U. dioica. The diet supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
11
0
3
Order By: Relevance
“…In addition, some studies have described benefits for U. dioica extract for management of diabetes complications [ 34 , 57 , 89 ]. More recently, it was demonstrated that supplementation with plain U. dioica led to body weight loss in mice that received a high-fat diet, via modulation of genes related to lipid and glucose metabolism [ 33 ]. In our study, the association of exercise with U. dioica extract significantly reduced the final body weight in OVX mice, and also improved the travelled distance and speed in an open arena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies have described benefits for U. dioica extract for management of diabetes complications [ 34 , 57 , 89 ]. More recently, it was demonstrated that supplementation with plain U. dioica led to body weight loss in mice that received a high-fat diet, via modulation of genes related to lipid and glucose metabolism [ 33 ]. In our study, the association of exercise with U. dioica extract significantly reduced the final body weight in OVX mice, and also improved the travelled distance and speed in an open arena.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds present in U. dioica extract include fatty acids, phenylpropanes, lignans, coumarins, triterpenes, ceramides, sterols, and lecithins [ 31 , 32 ]. Animals supplemented with U. dioica showed a reduction of adipose tissue accumulation, lower levels of fasting glucose and insulin, a decrease in HOMA-IR, and a reduction of liver triglycerides [ 33 ]. Compelling pre-clinical evidence revealed a hypoglycemic activity for the plant, and a meta-analysis carried out by Ziaie and collaborators (2019) corroborated the beneficial effects of U. dioica on glycemic levels.…”
Section: Introductionmentioning
confidence: 99%
“…The sample was subjected to nutrient composition analysis before incorporation into the diets. The dietary preparation, animal study procedures, and analytical procedures for tissues were as previously shown [ 17 ] and are briefly described in the following sections. Results of nutrient analysis by the Association of Analytical Chemists (AOAC) methods for calorific value and proximate analysis: moisture, ash, lipid, protein, carbohydrate, soluble fiber, insoluble fiber and fatty acid profile are shown in S1 and S2 Tables.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, U. dioica inhibited PP2A via a ceramide-independent mechanism. In support of the effects of U. dioica extract on activation of insulin signaling, leaf extract of U. dioica had hypoglycemic effects in normoglycemic rats [ 90 ] and attenuated glucose intolerance and improved insulin sensitivity in HFD-fed mice [ 89 , 91 ]. The active components mediating the anti-diabetic effects of this botanical preparation have not yet been determined.…”
Section: Inhibition Of Phosphatases For the Activation Of Insulin Signalingmentioning
confidence: 99%